Trajectories of women after completing STEM education: case of Kazakhstan (Journal of Educational Sciences, 2023)
The study analyzes the employment trajectories of women who have completed higher education programs in STEM fields (science, technology, engineering, and mathematics) in Kazakhstan. The aim of this research is to analyze the employment experiences of women with STEM education in Kazakhstan at their early stages of the careers, as well as to identify the factors that influence the career choices in the labor market. The study utilizes the results of individual semi-structured interviews that characterize various aspects of participants' work experiences based on their personal stories. The analysis revealed that the best employment outcomes and work experiences in STEM fields are observed among graduates who completed education programs in computer science and mathematics, while the highest rate of career attrition in the STEM field is found among graduates in engineering. Women who are confident in their STEM skills and professional competencies are more inclined to choose and remain in the STEM sector for employment. On the other hand, graduates who associate STEM education with increased difficulties and stress, as well as those who perceive their own competencies as insufficient for building a professional career in STEM segments of the labor market, are less likely to establish themselves in STEM fields. The results of the study indicate that women's expectations of success in STEM-related work directly influence the formation of subjective values associated with STEM careers and, as a result, their career choices. It was also discovered that cultural and gender-related factors, characteristic of the sociocultural peculiarities of Kazakhstan, are the most significant factors influencing the career choices of women graduates in STEM education programs.Key words: STEM graduates, employment of STEM graduates, employment in Kazakhstan, STEM higher education, trajectories of STEM graduates